Business Model Canvas : CartSmarter Enterprise Sdn Bhd / Amirah Syahirah Sukran - Sukran, Amirah Syahirah (2020)
A report of has been dedicated to discuss a Business Model Canvas (BMC) of CartSmarter Enterprise Sdn. Bhd. This report is required for New Product Development (NPD) commercialization proposal. At previous report on NPD proposal, CartSmarter has decided to introduce a new innovative product on existing shopping cart. The company want to launch GPSCart which is a smart navigation shopping cart. Thus, they have done go through all the NPD process to develop and launch the new shopping cart. One of important activities in NPD is test marketing process. Thus, a market survey by using google form survey has been conducted to know customer acceptance on GPSCart and its market potential. Based on the survey, The BMC is used to validate the market significance of products and services which will be of technology nature in this case. Thus, BMC can be used to visualize market problems and customer expectations. Technology projects are often solutions or processes that solve a technical problem. However, the market implementation of such solution is designed to overcome not just technical barriers also market and business-related barriers of costs, customer reach and collaborations and those that pertain to the practical nature of limited initial capacities within the team. This will make products or services more effective in market